Efficient Degradation of Industrial Biowaste via In-Vessel Composting—Technical and Microbial Assessments - Jamie Jean Minn Tan; Zi Xiang Keng; Siew Hui Chong; Guan-Ting Pan; Ajit Singh; Christinavimala Supramaniam; Ianatul Khoiroh (Bioengineering)
In this study, a pilot-scale in-vessel composter was used to treat a mixture of industrial biowaste, with soybean curd residue and saw dust as the major substrates. The composter is capable of treating up to 350 tons/month of waste, producing up to 150 tons/month of high-quality compost within a retention time of 7–10 days. The final compost has an average nitrogen–phosphorus–potassium content of 6%, moisture content of 28%, pH of 6.1, organic matter of 68%, and carbon–nitrogen ratio of 19:1. It also has a good amount of humic acid and macronutrients. Composts from all stages of the composting process—pre-mix, directly after discharge, after one-month of curing, and right before packaging—were evaluated with metagenomic analysis to identify the microbes that may add value to the compost.